Strategic Management Affecting Learning Organizations of School Under Nongkhai Primary Educational Service Area Office 2 - Sutthiprapa, Chana; Sonsupee, Sittichai (Journal of Graduate MCU KhonKaen Campus, 2023)
The purposes of this research were as follows: 1) to study the level of strategic management, 2) to study learning organization of school , and 3) to study the strategic management affecting learning organization of school under Nong Khai Primary Educational Service Area Office 2. The research samples consisted of two hundred and seventy-nine school administrators and teachers. which were selected by using stratified random sampling. The instruments used for this research was a questionnaire which the reliability of the questionnaire was at 0.980. The data analysis was performed by mean, standard deviation, and stepwise multiple regression analysis. The results of the research were as follows: 1) The level of strategic management among school administrators under Nong Khai Primary Educational Service Area Office 2 was at a high level as a whole. Considering each aspect, it was found that the aspect with the highest average was the Strategic Control and the lowest average was the Environment Analysis 2) The level of learning organization of school, the average was at a high level as a whole. Considering each aspect, it was found that the Professional Learning Community has the highest average and the lowest was Systems Thinking. 3) The strategic management affecting learning organization of school under Nong Khai Primary Educational Service Area Office 2. It was found that there were 4 components: Strategic Control, Strategic Implementation, Strategic Formulation and Environment Analysis. The multiple correlation coefficient was 0.729. The Learning Organizations predictive coefficient was 53.2% and a .05 level of statistical significance. A regression equation could be created in the form of a raw score. and standard scores.